The economic growth and inflation nexus: New empirical assessment for emerging market economies - Benjamin Kwaw Owusu; Bettina Bökemeier (Bielefeld University, Faculty of Business Administration and Economics, 2025)
This paper empirically studies the relationship between economic growth and inflation for a selected group of emerging market economies. We applied panel linear estimators, namely, static fixed effects and a dynamic GMM estimator to a sample of 31 countries. Our preliminary results point to the negative impact of inflation on economic growth. We further relaxed the linearity assumption and applied a dynamic threshold GMM model where the threshold variable (inflation) and other regressors are considered endogenous. Our subsequent results indicate that it is reasonable to distinguish between different inflation regimes, as we find a positive impact of inflation on economic growth in a low inflation regime. In contrast, high inflation exerts a negative effect on growth. Thus, we claim that inflation is not harmful to economic growth per se, but it needs to be considered in which inflation regime/situation the economy is situated. We find a threshold of about 2% above which inflation harms the economy.
urn:nbn:de:0070-pub-30070217
Keywords: O47; E31; 330; Economic Growth; Inflation; Emerging Markets; Panel Estimations; Panel threshold models